The Relationship Between Self-Esteem And Social Support On Cyber Bullying Behavior - Benny Kurniawan; Masayu Nandhia Dwiputri; Moersito Wimbo Wibowo (UNIVERSITAS PAKUAN, 2025)
This research aims to explore the relationship between self-esteem and social support on cyberbullying behavior among students. The research participants consisted of 120 students aged 18–22 years, 55 women and 65 men selected using purposive sampling techniques. Data collection was carried out using three instruments, namely the Rosenberg Self-Esteem Scale to measure the level of self-esteem, the Social Support Questionnaire to assess social support, and the Cyberbullying Behavior Scale to measure the intensity of cyberbullying behavior. The regression analysis results show that self-esteem has a significant negative effect on cyberbullying behavior (β = -0.202, t = -2.091, p = 0.039), which means that the higher an individual's self-esteem, the lower their tendency to commit cyberbullying. In contrast, social support had a significant positive effect on cyberbullying (β = 0.196, t = 2.031, p = 0.045), indicating that in some cases, certain social supports can increase involvement in cyberbullying. The simultaneous regression test shows that both variables contribute significantly to cyberbullying (F = 3.115, p = 0.048). The results of this research emphasize the importance of developing intervention programs that focus on increasing self-esteem and positive social support as preventive measures in reducing cyberbullying behavior among students.